Bank costs for decision making : costing procedures for pricing bank services - Walker, John R. (Boston : Bankers Pub. Co., 1970)
This book is on current bank accounting procedures and decision making purposes.
Bibliography: p. 114-115.
oo 23/01/2019
Loans
Keywords: Banks and banking; Banks and banking